2015
DOI: 10.1126/science.aaa9809
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric transcriptional regulation via changes in the overall topology of the core promoter

Abstract: Many transcriptional activators act at a distance from core promoter elements and work by recruiting RNA polymerase through protein-protein interactions. We show here how the prokaryotic regulatory protein CueR both represses and activates transcription by differentially modulating local DNA structure within the promoter. Structural studies reveal that the repressor state slightly bends the promoter DNA, precluding optimal RNA polymerase-promoter recognition. Upon binding a metal ion in the allosteric site, Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
238
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(247 citation statements)
references
References 65 publications
9
238
0
Order By: Relevance
“…At the molecular level, CueR likely achieves the biasing by distorting the DNA structure at the promoter. The bending and unwinding of DNA imposed by the holo-CueR (10,11,(13)(14)(15)(16)(17) are likely the structural basis for it to bias RNAP's kinetic sampling toward the open complex that we discovered here. Apo-CueR mainly bends the DNA at the recognition site and the structural changes differ from that imposed by holo-CueR (14); this different structural distortion could be the basis for apo-CueR's biasing RNAP toward sampling more of the dead-end complex.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…At the molecular level, CueR likely achieves the biasing by distorting the DNA structure at the promoter. The bending and unwinding of DNA imposed by the holo-CueR (10,11,(13)(14)(15)(16)(17) are likely the structural basis for it to bias RNAP's kinetic sampling toward the open complex that we discovered here. Apo-CueR mainly bends the DNA at the recognition site and the structural changes differ from that imposed by holo-CueR (14); this different structural distortion could be the basis for apo-CueR's biasing RNAP toward sampling more of the dead-end complex.…”
Section: Discussionmentioning
confidence: 91%
“…This distortion shortens the distance between the −35 and −10 elements and better aligns them for RNAP binding, thereby facilitating open complex formation and activating transcription. This DNA distortion mechanism for repressing and activating transcription (7,(10)(11)(12)(13)(14), so far unique to MerR-family metalloregulators, is confirmed by the protein crystal structures in complex with DNA (14-17), which show the bending and unwinding of the DNA in the repressed and activated states.The DNA distortion model has provided much insight into how metalloregulator-imposed DNA structural changes may affect RNAP−DNA interactions, especially for transcription activation. Little is known, however, on how metalloregulator−DNA interactions are coupled dynamically to RNAP−DNA interactions for transcription initiation.…”
mentioning
confidence: 75%
“…In contrast, the cytoplasm is not predicted to require copper (10,11). This compartment is monitored by the copper-efflux regulator CueR, a MerR-like transcription factor that mounts the response to eliminate the toxic ion from the cytoplasm (12); thus, the independent monitoring of copper in each compartment provides a physiological advantage, allowing maintenance of the appropriate quota in the envelope and its exclusion from the cytoplasm.…”
mentioning
confidence: 99%
“…The RI1 of MerR is located within two known domains: MerR (Pfam PF00376), positioned between residues 1–24, and the DNA-binding domain MerR-type helix-turn-helix domain (Prosite PS50937), positioned between residues 1–43. A homologue of MerR – the copper efflux regulator homodimer (PDB 4WLS) of Escherichia coli – was recently crystalized with DNA [18] and was shown to be a dimer comprising two N-terminal DNA binding domains connected by a dimerization helix [18]. Our analysis revealed that RI1 is located within the dimerization helix of MerR (Figure 2(C)); thus, the B. melitensis strain 16M, which lacks RI1, may possess a deficient dimerization of the DNA binding domain.…”
Section: Resultsmentioning
confidence: 99%